Telling Tales’: Stories, Metaphors and New Knowledge at the Front-End of NPD - Sakellariou, Evy; Karantinou, Kalipso; Goffin, Keith (Wiley, 2017)
Breakthrough ideas depend upon the generation of new knowledge, which emerge from the conversion of tacit knowledge at the fuzzy front‐end (FFE) of new product development (NPD). The occurrence of stories and metaphors has been strongly linked to tacit knowledge, however, empirical studies that examine how stories and metaphors harness tacit knowledge in the FFE are lacking. In addition, how managers can use stories and metaphors to develop breakthrough product ideas is unclear. To address these gaps, an ‘in‐situ’ empirical case study was conducted in the European subsidiary of a B2C multinational. This study investigated the role, characteristics and interplay of stories and metaphors emerging in discussions between managers and customers in a collaborative design workshop (CDW). Taking a knowledge management theoretical perspective, the data were analyzed using the well‐known SECI framework. The results clearly show that significant new knowledge was created based on the discussions in a CDW and stories and metaphors were important mechanisms for this. Importantly, it was stories related to product usage that triggered breakthrough ideas. The study extends the understanding of how breakthrough ideas emerge; it proposes a tentative conceptual framework; and it provides managers with recommendations of how to use stories and metaphors effectively during the FFE.